-5y-1=4y-7

Simple and best practice solution for -5y-1=4y-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5y-1=4y-7 equation:



-5y-1=4y-7
We move all terms to the left:
-5y-1-(4y-7)=0
We get rid of parentheses
-5y-4y+7-1=0
We add all the numbers together, and all the variables
-9y+6=0
We move all terms containing y to the left, all other terms to the right
-9y=-6
y=-6/-9
y=2/3

See similar equations:

| 6(m+11=96 | | 3-(0.25x)=(-0.5x)+9 | | 0.10(y-3)+0.20y=0.06y-1.2 | | t/6+73=81 | | 154/c=2 | | 3-(0.25x)=-0.5x9 | | 4(2y-10)=4 | | 5(2x+8)=-26+46 | | 2(x+10)+7x=9x | | 90=20x+10 | | 3z2−12z=0 | | 4x=0+6 | | 4(m+7)=16 | | b/4+20=23 | | 7x+2+5x-3=2x+6 | | 3x-10+20=-11 | | 17=v/3+14 | | 7x+2+2x+6=5x-3 | | u/2+16=20 | | 7-3r=15 | | 26=104/f | | 10(z+63)-98=-68 | | 81=3(d+20) | | 2b-24=9 | | -2x+8=(-3x)-1 | | 3x=18-(6x+27) | | 4s−3=9 | | 70=7(p+7) | | 2(u-99)=8 | | -3(2x-3)+4=27-× | | 36=9(j-86) | | m/2-10=-7m= |

Equations solver categories